'Two clicks and I'm in!' Patients as co-actors in managing health data through a personal health record infrastructure. (June 2019) - Zanutto, Alberto
One of the most significant changes in the healthcare field in the past 10 years has been the large-scale digitalization of patients' healthcare data, and an increasing emphasis on the importance of patients' roles in cooperating with healthcare professionals through digital infrastructures. A project carried out in the North of Italy with the aim of creating a personal health record has been evaluated over the course of 5 years by means of mixed method fieldwork. Two years after the infrastructure was put into regular service, the way in which patients are represented in the system and patient practices have been studied using surveys and qualitative interviews. The data show that, first, patients have become co-actors in describing their clinical histories; second, that they have become co-actors in the diagnosis process; and finally, they have become co-actors in the management of time and space as regards their specific state of health.